Seven little rabbits - Becker, John Leonard, 1901-; Cooney, Barbara, 1917- (New York, Scholastic Inc. by arrangement with Walker & Company, 1973)
One by one, as they walk down the road, seven little rabbits get tired and find a place to sleep.
Booklist
Library Journal
Kirkus Reviews
4.1
K-3
Keywords: Rabbits -- Poetry; Rabbits -- Fiction